Using cost-analyses to inform health professions education – The economic cost of pre-clinical failure. (2nd December 2018) - Foo, Jonathan; Ilic, Dragan; Rivers, George; Evans, Darrell J. R.; Walsh, Kieran; Haines, Terry P.; Paynter, Sophie; Morgan, Prue; Maloney, Stephen
Abstract: Background: Student failure creates additional economic costs. Knowing the cost of failure helps to frame its economic burden relative to other educational issues, providing an evidence-base to guide priority setting and allocation of resources. The Ingredients Method is a cost-analysis approach which has been previously applied to health professions education research. In this study, the Ingredients Method is introduced, and applied to a case study, investigating the cost of pre-clinical student failure. Methods: The four step Ingredients Method was introduced and applied: (1) identify and specify resource items, (2) measure volume of resources in natural units, (3) assign monetary prices to resource items, and (4) analyze and report costs. Calculations were based on a physiotherapy program at an Australian university. Results: The cost of failure was £5991 per failing student, distributed across students (70%), the government (21%), and the university (8%). If the cost of failure and attrition is distributed among the remaining continuing cohort, the cost per continuing student educated increases from £9923 to £11, 391 per semester. Conclusions: The economics of health professions education is complex. Researchers should consider both accuracy and feasibility in their costing approach, toward the goal of better informing cost-conscious decision-making.